Analisis Kesulitan Siswa Kelas VI dalam Menulis Naskah Pidato Sebagai Alternatif Pembuatan Media Pembelajaran - Nuraeni, Nuraeni; Wardana, Deni; Widjojoko, Widjojoko (Didaktika, 2021)
Writing skills may be defined as an activity for delivering messages (communication) by using written language as a medium or device. In the world of education especially in elementary school writing skills are the last of the skills in the process of learning language skills after those of listening, speaking, and reading. Of the four language skills, a student must master, most are experienced by the student with the difficulty of mastering writing skills. Difficulty writing will hinder students from pouring ideas, ideas, and thoughts through the medium. The study is intended to know, analyze, and describe the difficulties experienced by students in writing the speech text in class VI SDN Karodangan class 2020/2021 and create a learning media of animation videos based on difficulties experienced by students. The method used is the method of content analysis aimed at analyzing phenomena based on documents obtained from research. The subject of this study is a document of a student's eulogy. The data-gathering techniques of this study are participant observations, in-depth interviews, and document analysis. The results of this study are the students' difficulties in repeating ideas, difficulties in choosing appropriate words/diction, difficulties in shaping themes, and difficulties in completing systemic speech.